Arguments to Critique Transformative Learning Theory - Poohongthong, Chanadda (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2023)
The aim of this paper is to develop arguments to critique Jack Mezirow’s transformative learning theory, which relate with the issues of Jürgen Habermas’s rationality and validity claim. Research methodology in this study is documentary research and using document analysis. This research methodology will be the documentary research and employ the qualitative criterion of managing data sources to collect and interpret the qualitative data. The primary sources are Habermas’ The theory of communicative action: Volume One and Volume Two (Habermas, 1984, 1987) and Mezirow’ major works on transformative learning theory (Mezirow, 1985, 1990, 1991a, 1991b, 1996), including seven other secondary sources (Calleja, 2014; Dirkx, 1998; Fleming, 2005, 2018, 2020; Taylor, 1997; Taylor & Cranton, 2012). For the qualitative data analysis, it found that four arguments emerged: (1) Mezirow emphasized social dimension through discourse for transformation at the levels of individual and group; (2) cognitive and logical processes as a part of Habermas’s rationality; (3) Mezirow recognized and accepted emotional dimension in discourse; and (4) dividing emotional dimension in only two types (positive and negative emotions) can possibly become a constraint of emotional dimension in transformative learning theory. These were due to connection between Habermas’ aspects of rationality, types of action, and forms of validity claim that are the theoretical roots of significant elements in Mezirow’s transformative learning theory, especially in dimensions of learning, critical reflection, and discourse.